2006
DOI: 10.1590/s0103-64402006000200005
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopic analysis of the effect of CarisolvTM gel on periodontally compromised human root surfaces

Abstract: The aim of this study was to analyze, under scanning electron microscopy (SEM), the morphologic characteristics of root surfaces after application of Carisolv TM gel in association with scaling and root planing (SRP). Sixty periodontally compromised extracted human teeth were randomly assigned to 6 groups: 1) SRP alone; 2) passive topical application of Carisolv TM + SRP; 3) active topical application of Carisolv TM + SRP; 4) multiple applications of Carisolv TM + SRP; 5) SRP + 24% EDTA; 6) topical application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(25 reference statements)
3
1
0
Order By: Relevance
“…The application of chemo-mechanical therapy resulted in the elimination of the infected cementum along with the exposure of the unaffected cementum, as evidenced by the specimens treated with EDTA-S in the current experiment, which had a mosaic-like appearance showing the cementum. This was consistent with a prior investigation conducted by Grisi et al 17…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The application of chemo-mechanical therapy resulted in the elimination of the infected cementum along with the exposure of the unaffected cementum, as evidenced by the specimens treated with EDTA-S in the current experiment, which had a mosaic-like appearance showing the cementum. This was consistent with a prior investigation conducted by Grisi et al 17…”
Section: Discussionsupporting
confidence: 94%
“…16 The application of chemo-mechanical therapy resulted in the elimination of the infected cementum along with the exposure of the unaffected cementum, as evidenced by the specimens treated with EDTA-S in the current experiment, which had a mosaic-like appearance showing the cementum. This was consistent with a prior investigation conducted by Grisi et al 17 Dentinal tubule patency was seen in the EDTA-S group at a magnification of 1500´. The dentinal tubule integrity could be visible even at a magnification of 200´, according to an investigation conducted by Banerjee et al 18 This was not observed in line with research by Grisi et al 17 The dentinal tubules of the EDTA group were found to be less permeable than those of the EDTA-S group at a magnification of 1500´.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, multiple applications of Carisolv™ combined with SRP procedures could remove the contaminated cementum and expose its healthy structure (13).…”
Section: Introductionmentioning
confidence: 99%